Pb2+ removal based on the confinement effect in polygonal carbon nanotubes: a molecular dynamics simulation. Issue 6 (26th January 2023) - Yan, Zhiguo; Liu, Jieqing; Huang, Ling; Fu, Heqing
Abstract : Polygonal carbon nanotubes/graphene are promising composite materials for Pb 2+ interception at the outlets. Abstract : Heavy metal Pb 2+ pollutants have become an important environmental problem, which threatens public health and ecosystems worldwide. In this study, to explore the effective treatment of trace Pb 2+ pollution in water, molecular dynamics simulation combined with DFT calculations was used to study the transportation behavior of Pb 2+ using polygonal carbon nanotubes (PCNT: P = 4, 5, 6, 8)/graphene composites (PCNTs/G). It is shown that due to the confinement effect of PCNTs, both H2 O and H3 O + can form a hydrogen-bonding network and transport them in the form of proton exchange through the PCNT channels. The trajectory shows that with the help of a hydrogen-bonding network, the probability of Pb 2+ passing through the 8N channel is enhanced. Then, upon the fluorine modification of PCNTs, mutual effects of both the hydrogen-bonding network and electrophilic attraction make Pb 2+ get through the channel of 8F. It is indicated that with respect to 4CNT/G, 5CNT/G, and 6CNT/G, 8CNT/G is not accurate for Pb 2+ interception at the outlets. In addition, the RDF, and HOMO–LUMO orbitals indicate that the affinity from the hydrogen-bonding network and PCNT walls both play important roles in particle transportation. This work can not only provide a basic understanding of Pb 2+ transportation in PCNTs from the perspective of diffusion but also be helpful to guide the strategy on how to deal with Pb 2+ pollution in waters.